Etika Digital dalam Kode Etik Guru: Tren Penelitian dan Implikasinya terhadap Profesionalisme Pendidik pada Era Artificial Intelligence - Muhammad Ainul Wildan; Livie Izzati Hasanah; Munawir (STKIP Subang, 2026)
The development of digital technology and Artificial Intelligence (AI) has created new challenges for implementing teachers’ professional codes of ethics in educational practices. This study aims to analyze research trends on digital ethics within teachers’ codes of ethics, identify major issues and challenges, and examine their implications for teacher professionalism in the AI era. The study employed a library research method with a descriptive qualitative approach using the Narrative Literature Review model. Data were collected from 25 scholarly articles published between 2020 and 2026 and indexed in Google Scholar, SINTA, GARUDA, and related academic databases. The findings reveal a shift in research focus from digital competence toward digital ethics and AI utilization in education. Key issues include data protection, academic integrity, digital literacy, digital communication ethics, and professional responsibility. The study concludes that digital ethics plays a strategic role in strengthening teacher professionalism through enhanced integrity, accountability, technological adaptability, and public trust.